2022
DOI: 10.1002/ece3.9353
|View full text |Cite
|
Sign up to set email alerts
|

No relationship between chronotype and timing of breeding when variation in daily activity patterns across the breeding season is taken into account

Abstract: There is increasing evidence that individuals are consistent in the timing of their daily activities, and that individual variation in temporal behavior is related to the timing of reproduction. However, it remains unclear whether observed patterns relate to the timing of the onset of activity or whether an early onset of activity extends the time that is available for foraging. This may then again facilitate reproduction. Furthermore, the timing of activity onset and offset may vary across the breeding season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Our study is among the few that have identified fitness correlates of (relative) chronotype in female animals. We firstly show high repeatability of timing, and thus corroborate evidence of chronotype as a consistent individual trait in birds, including in our study species (Graham et al, 2017; Meijdam et al, 2022; Stuber et al, 2015). We then show that the relative chronotype of female great tits, measured during the incubation period, predicted reproductive success, such that early-rising females raised more offspring to fledging than late (relative) chronotypes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our study is among the few that have identified fitness correlates of (relative) chronotype in female animals. We firstly show high repeatability of timing, and thus corroborate evidence of chronotype as a consistent individual trait in birds, including in our study species (Graham et al, 2017; Meijdam et al, 2022; Stuber et al, 2015). We then show that the relative chronotype of female great tits, measured during the incubation period, predicted reproductive success, such that early-rising females raised more offspring to fledging than late (relative) chronotypes.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we leverage data from wild birds to i) disentangle factors that contribute to explain variation in clock and relative chronotype, and ii) newly document links between chronotype and reproductive success. Here, we examine a well-studied songbird whose chronotype has been shown to be repeatable, the great tit ( Parus major; Graham et al, 2017; Meijdam et al, 2022; Stuber et al, 2015). We inferred female chronotype through measuring behaviour during incubation, a critically important post-zygotic stage of avian reproduction, while monitoring reproductive success (Capilla-Lasheras, 2018; Graham et al, 2017; Gwinner et al, 2018; Maury et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From the total of 1076 observations 5 datapoints were collected using the infrared cameras (1 in 2018, 4 in 2021), 49 using the RFID loggers (9 in 2018, 40 in 2020) and all remaining data via SongMeters (see also 39 for more details on the data selection process). We removed one datapoint from the dataset as it was an outlier.…”
Section: Methodsmentioning
confidence: 99%